The use of biographical narratives to explain favourable and unfavourable outcomes for children in foster care. (March 2015) - Reimer, Daniela; Schäfer, Dirk
In many European countries, the number of children living in foster families temporarily or for longer periods is rising, but little is known about the experiences and feelings of children growing up in these settings and whether or how these are related to outcomes. This article seeks to fill this gap by discussing the views of former foster children as reported in autobiographical interviews. It expands research on biographical narratives and life courses, as well as theories of social pedagogy concerned with risk and protective factors, by exploring young people's perceptions, interpretations and coping strategies alongside critical events and turning points in their lives. A distinctive feature of the approach is the inclusion of objective and subjective dimensions of favourable or unfavourable life courses. Four biographies are summarised to represent these. The article closes with a discussion of the significance for foster care of five issues identified in the analysis: precarious biographical episodes, socialisation, continuity, participation and coping strategies.